2011
DOI: 10.1155/2011/176813
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational Protein Folding and Terminus Hydrophobicity

Abstract: Peptides fold on a time scale that is much smaller than the time required for synthesis, whence all proteins potentially fold cotranslationally to some degree (followed by additional folding events after release from the ribosome). In this paper, in three different ways, we find that cotranslational folding success is associated with higher hydrophobicity at the N-terminus than at the C-terminus. First, we fold simple HP models on a square lattice and observe that HP sequences that fold better cotranslationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the positioning of hydrophobic clusters in the sequence may affect the folding pathway and dynamics e.g. [ 2 , 3 ]. Note that these stabilizing forces are partially compensated by the decrease in chain entropy upon folding.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the positioning of hydrophobic clusters in the sequence may affect the folding pathway and dynamics e.g. [ 2 , 3 ]. Note that these stabilizing forces are partially compensated by the decrease in chain entropy upon folding.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, at least in some cases, cotranslational folding requires complete protein structural subdomains [107] , [108] . Cotranslational protein folding following the sense of translation (from the N terminal) predicts more accurately protein structures than when proceeding in the opposite sense (from the C terminal) [109] , [110] , indicating that cotranslational protein folding is a reality for most proteins. Nevertheless, cell free protein folding shows that cotranslational folding is not always required [111] .…”
Section: Translation Kineticsmentioning
confidence: 99%
“…The cotranslational folding process is controlled by translation speed and special ribosomal structure 2 13 14 15 16 . Experimental and theoretical studies on the cotranslational folding were highlighted and novel phenomena were observed 7 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 . For examples, it was found that the synthesized peptides take on definite secondary structures while they are growing on the ribosome 2 16 .…”
mentioning
confidence: 99%